Association of lung cancer with ecological and biochemical factors a clinico epidemiological study. - Thakur, Binay Kumar (2011)
ABSTRACT: Background: During the period of last many years, Lung cancer has become one of the most serious problems indicating actual and social issues of people, as the incidence of lung cancer has increased by three times in last three decades. In the contemporary conditions of modern era, it is becoming more obvious that there is a trend towards more advanced stage and poor prognosis in young age leading to more mortality. The later indicated the inadequate efficacy of the preventive measures and treatment modalities. The purpose of the study is to carry out clinic-epidemiological analysis of cause-effect relationship of lung cancer with the ecological and biochemical factors within the territories of Chuvash republic of Russian Federation and Nepal. The main objectives are: 1. To accomplish clinic-epidemiological monitoring of prevalence of lung cancer among the population of Chuvash republic and Nepal. 2. To study the conditions of water supply, nutritional status and life style of the population of experimental and control groups of biogeochemical provinces in the limits of the studied territories. 3. To carry out the comparative clinical analysis of the course of lung cancer among the population, which lives under different ecological-biogeochemical conditions of Chuvash and Nepal 4. To find out the changes in some of the important biochemical factors in the human body of different population groups (healthy people and people suffering from lung cancer). 5. To come up with the recommendation regarding the primary prevention of lung cancer in Chuvash republic and Nepal. Materials and methods: The methodology includes the following steps: 1. study of the incidence of the disease in the given territories of research 2. Division of the territories on the basis of ecological and biogeochemical factors 3. Comparative study of the condition of water, food and nutrition, pattern of job and life style among population of control and experimental territories 4. Comparative physiological and hygienic study of biochemical, hormonal , immunological and microbiological factors among practically healthy population of experimental and control territories 5. Correlation and multivariate regression-dispersion analysis of association of factors of living environment with the index of prevalence of the disease 6. Comparative analysis of clinical aspects of the disease among the population in the experimental and control territories. 7. Study of trace elements in blood, urine, saliva, tears, nail, resected lung specimen and hair in patients with the disease from experimental and control territories. For epidemiological study of cause-effect relationship between lung cancer and ecologo biogeochemical factors, Vurnar administrative region (Chuvash republic), Russian Federation) and Bharatpur (Chitwan district, Nepal) have been taken as''experimental/study group'' and Kolsovo administrative region (Chuvash republic, Russian Federation) and Tansen (Palpa distric, Nepal) have been taken as'' control group.'' The population of both the groups has been matched for age, sex, nationality, and occupation. Results: The high incidence of lung cancer has been found in Vurnar region 9326.8/100000 population) of Chuvash republic and Chitwan, Rupandehi, Nabalparasi districts (approx, 500/100000 population), Increased level of Si, Mn, Cd, and F has been found in drinking water of study group of Chuvash and Nepal (p<0.05). The comparative analysis of samples of hair from lung cancer patients of study group and practically healthy people from control group of both Chuvash and Nepal has shown lower level of Ca, Zn, Co, Mo, Se and Cr and higher levels of As, Cd and Pb (p<0.05). Statistically significant lower levels of Zn, Se, Co and Mo and higher levels of As, Li, Cd and Pb have been found in surgically resected cancerous tissue in comparison to the normal lung tissue of patients with non-small cell lung cancer. Conclusion: 1. The incidence of lung cancer in Nepal and Chuvash republic of Russian Federation is different in different regions. It depends upon the difference in ecologobiogeochemical factors. The highest incidence of lung cancer has been registered in Vurnar, Apner regions of Chuvash republic (80.9-100.1/10000 population) and in Chitwan district of Nepal (80/10000 population). These regions have been considered as the ''study group''. The lowest incidence has been found in Kolsovo, Chuvash (<19.6/ 10000 population) and in Palpa (6.0/ 10000 population). These regions have been considered as ''Control group''. 2. Biogeochemical analysis of drinking water and food products, consumed by people of study and control groups showed statistically significant difference in the level and ratio of various macro and trace elements. 3. Comparative analysis of clinical features showed identical symptoms and signs in with radiation, whereas in Nepal, symptomatic treatment was common. 4. Results showed a difference in level of trace elements in hair of the study group in comparison to the control group. Various pathogenic microflora were identified in bronchial lavage of lung cancer patients. Broncheoalveolar lavage was sterile in healthy people. 5. Level of certain trace elements differed in the cancerous part in comparison to non-cancerous part of surgically resected lung parenchyma. Keywords: Lung cancer, trace elements, pulmonary resection